2020
DOI: 10.1242/jeb.226233
|View full text |Cite
|
Sign up to set email alerts
|

High temperature induces transcriptomic changes inCrassostrea gigasthat hinders progress of Ostreid herpesvirus (OsHV-1) and promotes survival

Abstract: Among all the environmental factors, seawater temperature plays a decisive role in triggering marine diseases. Like fever in vertebrates, high seawater temperature could modulate the host response to the pathogens in ectothermic animals. In France, massive mortality of Pacific oysters Crassostrea gigas caused by the ostreid herpesvirus 1 (OsHV-1) is markedly reduced when temperatures exceed 24°C in the field. In the present study we assess how high temperature influences the host response to the pathogen by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 75 publications
(80 reference statements)
1
25
0
Order By: Relevance
“…Alternatively, the different temperatures (18 • C for abalone and 15 • C for clam) we applied during infections could lead to differential infection dynamics [44,45]. These temperatures were, however, chosen to resemble the environmental conditions for which mortalities were observed, and are similar to the temperature threshold necessary for OsHV-1 to cause disease in oysters (16 • C) [46], whereas only much higher temperatures (24 • C) were shown to limit the progression of OsHV-1 infection [47]. It is therefore unlikely that infection dynamics during mortalities in both hosts differ substantially from our experimental infections.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the different temperatures (18 • C for abalone and 15 • C for clam) we applied during infections could lead to differential infection dynamics [44,45]. These temperatures were, however, chosen to resemble the environmental conditions for which mortalities were observed, and are similar to the temperature threshold necessary for OsHV-1 to cause disease in oysters (16 • C) [46], whereas only much higher temperatures (24 • C) were shown to limit the progression of OsHV-1 infection [47]. It is therefore unlikely that infection dynamics during mortalities in both hosts differ substantially from our experimental infections.…”
Section: Discussionmentioning
confidence: 99%
“…To infect oysters, authors performed experimental injections of OsHV-1 in the adductor muscle of Pacific oysters, an experimental approach developed by Schikorski et al. ( 11 ) which is routinely used to evaluate in vivo interactions between C. gigas and OsHV-1 ( 33 , 39 41 ). Infection by injection provides a better synchronization of the viral infection compared to natural infections.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of viral infection, ubiquitin-related proteins coordinate an effective antiviral immune response by regulating efficient antiviral signaling pathways such as the RIG-I-like, Toll-like or interferon-like pathways ( 80 ). Several studies showed that genes related to the ubiquitination process increased during the first hours of infection (6 and 12 hpi) with a higher expression in more resistant compared to more susceptible Pacific oysters ( 20 , 41 , 79 ). In our study ubiquitin-related proteins were highly modulated in the more resistant Pacific oysters, while few of them were modulated in the more susceptible Pacific oysters.…”
Section: Discussionmentioning
confidence: 99%
“…bacterial virulence or oyster physiology) could be influenced by high temperatures and thereby affect POMS permissiveness. Although the effect of high temperatures on bacterial virulence remains to be investigated, a recent work demonstrated that oyster immunity is modulated, and apoptotic processes induced, by high temperatures, which could explain the observed decrease of permissiveness ( 11 ).…”
Section: Poms Is a Multifactorial Diseasementioning
confidence: 99%